2015
DOI: 10.1097/phm.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Resident-Perceived Benefit of a Diagnostic and Interventional Musculoskeletal Ultrasound Curriculum

Abstract: Musculoskeletal ultrasound (MSUS) training is now a required component of physiatry residency, but formal curriculum guidelines are not yet required or established. The authors’ objective was to assess the educational value of a collaborative residency MSUS training program. The authors designed a structured MSUS training curriculum for residents based on the authors’ experience and previous literature. Twenty-five residents participated in this MSUS curriculum designed by faculty and chief residents. Resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Near-peer teaching of learners by senior trainees can supplement preceptor-mediated training. 33,34 Meanwhile, MSKUS training opportunities are expanding through professional associations' clinician certificate programs and train-the-trainer sessions (eg, American Academy of Physical Medicine and Rehabilitation's STEP: Skills, Training, Evaluation and Performance, American Association of Neuromuscular and Electrodiagnostic Medicine's Neuromuscular Ultrasound Workshops, AAP's Faculty Development course on Teaching MSKUS Education). This is important because our survey data show a possible bias toward programs having a structured curriculum if the program director performs MSKUS himself/herself.…”
Section: Discussionmentioning
confidence: 99%
“…Near-peer teaching of learners by senior trainees can supplement preceptor-mediated training. 33,34 Meanwhile, MSKUS training opportunities are expanding through professional associations' clinician certificate programs and train-the-trainer sessions (eg, American Academy of Physical Medicine and Rehabilitation's STEP: Skills, Training, Evaluation and Performance, American Association of Neuromuscular and Electrodiagnostic Medicine's Neuromuscular Ultrasound Workshops, AAP's Faculty Development course on Teaching MSKUS Education). This is important because our survey data show a possible bias toward programs having a structured curriculum if the program director performs MSKUS himself/herself.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study by Luz et al [ 19 ] showed that after presenting training courses in the curriculum, the knowledge level of residents in neuromusculoskeletal sonography increased significantly, to the extent that 86% of the residents who participated in the study claimed ultrasound training to be “very necessary” or “definitely essential”. Also, 73% of them considered self-learning of this skill to be “useful” or “very useful”.…”
Section: Discussionmentioning
confidence: 99%
“…Stoven et al [ 18 ] also suggested the addition of sonography as an important training subject for internal medicine residents. The studies performed by Coris [ 3 ], Luz [ 19 ], and Arger [ 20 ] also emphasize the effectiveness, accuracy, and cost-effectiveness of ultrasonography in the field of musculoskeletal disorders and deem it essential for physicians to receive sufficient training.…”
Section: Introductionmentioning
confidence: 99%
“…Direct observation of resident teachers also allows the Residency's Clinical Competency Committee to better assess a resident's progression through the Practice-Based Learning and Improvement Milestone 1 [19]. It has previously been demonstrated that utilizing PM&R residents as teachers in musculoskeletal care is well received by the learners [20]. …”
Section: Discussionmentioning
confidence: 99%